2c+3+4d-c+d=

Simple and best practice solution for 2c+3+4d-c+d= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c+3+4d-c+d= equation:


Simplifying
2c + 3 + 4d + -1c + d = 0

Reorder the terms:
3 + 2c + -1c + 4d + d = 0

Combine like terms: 2c + -1c = 1c
3 + 1c + 4d + d = 0

Combine like terms: 4d + d = 5d
3 + 1c + 5d = 0

Solving
3 + 1c + 5d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + 1c + -3 + 5d = 0 + -3

Reorder the terms:
3 + -3 + 1c + 5d = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 1c + 5d = 0 + -3
1c + 5d = 0 + -3

Combine like terms: 0 + -3 = -3
1c + 5d = -3

Add '-5d' to each side of the equation.
1c + 5d + -5d = -3 + -5d

Combine like terms: 5d + -5d = 0
1c + 0 = -3 + -5d
1c = -3 + -5d

Divide each side by '1'.
c = -3 + -5d

Simplifying
c = -3 + -5d

See similar equations:

| 6x^2=55x | | X^2+y^2-7=0 | | 5c+4d-c+d= | | 10+7x=-74 | | e^5x+7=10 | | Y+4+y-6=66 | | 5.7+77=8.2+12 | | 2(2x-1)=22 | | y=0.04t | | X^2+kx=28 | | 8=2x+7 | | f+(1/2f)=15 | | 4.8+1.2=1.92 | | 5.6-7.4=8.84 | | 9t-21=9t-21 | | -7x-10y=-68 | | 2a^2=13a+7 | | -7x-23=135 | | ln(7x+6)=1 | | (7x+6)=1 | | (16-8y)=x | | .5x+.21(200)=.25(132) | | 7x+(2x)+x=42 | | .8(x+30)+.2x=50 | | D(t)=-16t^2+32t+24 | | .48(6)+.08x=.16(30+x) | | 3-log(5x+1)=0 | | 5x^2-xy-4y^2=0 | | .55x+.45(4-x)=.6(-1) | | 3(2x-4)=4x+18 | | -4+8m=36 | | 4x^2-2x-0=0 |

Equations solver categories